Efficiency of the endovenous cyanoacrylate for the treatment of varicose veins using the VenablockTM system: a 24 months follow-up study of 116 patients - Düzgün, Ali Cemal; İlkeli, Ekin and Katırcıoğlu, Fehmi (The European Research Journal, 2021)
Objectives: Dilation of superficial veins and valvular insufficiency cause the common condition, varicose veins (VVs) on the lower extremities. The treatment modalities for VVS include endovascular thermal ablation techniques using laser, steam and radiofrequency, surgery, foam sclerotherapy, which has various adverse effects. N-butyl cyanoacrylate (NBCA) is a relatively novel polymerizating agent that is used for the treatment of VVs. The aim of this study is to evaluate and present the 24 months outcomes results of endovenous NBCA treatment in 116 patients with VV. Methods: This is a prospective study on 116 patients (71 females, 45 males), treated in a single-center between August 2017 and March 2019. NBCA administration (Venablock®, Invamed, Turkey) was carried out with local anesthesia under ultrasound guidance. All patients were scheduled for follow-up evaluation at 2 weeks, 3, 6, 9, 12, and 24 months. Clinical assessment, VCSS, and ultrasound were performed on patients in the follow-up visits. Results: The mean follow-up period was 16.27 ± 5.62 months. The preoperative and postoperative VCSS values were 6.93 ± 2.60 and 2.40 ± 1.12, respectively (p < 0.0001). The patients with a greater GSV diameter experienced an unfavorable outcome following the NBCA procedure (p < 0.001). The overall complication rate was 12.9%. The complete occlusion was achieved in 101 (87.0%) patients. Conclusions: The NBCA administration is a safe treatment method for the VVs, and provides a satisfactory occlusion ratio with improved outcomes.